Linguacultural Analysis of Language of Advertising in the English Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is dedicated to the study of advertising discourse in the American variant of the English language. Advertising is a reflection of the culture of a country, its mentality, and national character, in which all socio-cultural phenomena are reflected. The study reveals not only the lingua-cultural features of advertising slogans, but also conducts their lingua-stylistic analysis with the aim of identifying the cultural characteristics of American society.